Suicidal Ideation Among Undergraduates in Ibadan: Examining the Influence of Depression and Hopelessness - Charles A. Ayeni; Esohe G. Ehondor; Kehinde H. Mobolaji; Nurudeen Y. Ariwoola; Emmanuel E. Uye (International Journal of Technology and Education Research, 2025)
This study examines the influence of depression and hopelessness on suicidal ideation among undergraduates of the University of Ibadan, Nigeria. The study adopted cross-sectional survey design while purposive sampling technique was used to select the study population. Data were conveniently collected from 200 participants using validated questionnaires and analyzed using zero-order correlation and independent sample t-test statistics and accepted at p <.001 level of significance. The result revealed that depression (r=-.23, p <.00) and hopelessness (r=-.32, p <.001) negatively correlated with suicidal ideation among study participants. Furthermore, both depression [t (197) =-3.65, p < .001] and hopelessness [t(197) = -4.85, p <0.001] significantly contributed to suicidal ideation among study participants. However, there was no gender difference in suicidal ideation among study participants. The study concludes that depression and hopelessness strongly correlated with suicidal ideation among undergraduates of the University of Ibadan. The study recommends that the university authority should have a functional mental health clinic to attend to students diagnosed with suicidal thoughts and other psychological dysfunctions.